An Investigation Whether and How Christian Organizations Respond to the Practical Needs of Students with Disabilities: A Case of One College in Zomba - Kamchedzera, Elizabeth T. (Journal of disability & religion, 2016)
This article investigates whether and how Christian organizations respond to the practical needs of students with disabilities in one of the constituent colleges of the University of Malawi. First, the article identifies the practical needs of the students with disabilities. Second, the article investigates whether and how the Christian organizations respond to the practical needs of such students in the campus. Located within the interpretative paradigm, the article adopted qualitative methodology to investigate the issues at hand using semi-structured interviews with the leaders of the Christian organizations on the campus and focus group interviews with the students with disabilities. Data were analyzed using thematic analysis. The key findings have revealed that the practical needs of students with disabilities are spiritual needs, support, accommodation and participation, academic needs, and association and interaction. It was further revealed that although the students with disabilities were included in some of the large Christian organizations, some of their needs were not responded to. These key findings are discussed to inform any changes that the religious organizations working on campus might make in response to the practical needs of students with disabilities, bearing in mind that Jesus ministered to people with disabilities as well. The change may also enhance their spiritual growth and, in turn, testify to what God has done for them through such Christian organizations; it may also enable them to help others, too.